Unlocking the power of play: exploring the benefits of traditional games for adapted sports in people with cerebral palsy: a scoping review - Mansoor Rahman A; Jagadish Kumar (Physiotherapy Quarterly)
Introduction Adapted physical education is a viable way to improve physical activity in individuals with cerebral palsy. While there is adequate documentation on adapting western games, low- and middle-income countries may lack these resources. Traditional games deeply ingrained in these nations, can be played informally with minimal equipment. Adapting traditional games can be an effective way to increase activity and participation. This review presents the existing body of knowledge and identifies the benefits of traditional games in the context of adapting traditional games for individuals with cerebral palsy.